PENINGKATAN NILAI PRODUK HARD CANDY JAHE (ZINGIBER OFFICINALE ROSC.) MELALUI PENDAMPINGAN PENGEMASAN DI DESA MURTAJIH, KECAMATAN PADEMAWU, KABUPATEN PAMEKASAN - Iffan Maflahah; Darimiyya Hidayati; Cahyo Indarto; Muhammad Fuad Fauzul Mu`tamar; Sinar Suryawati; Burhan (LP2M Universitas Hasanuddin, 2023)
Ginger can be used as hard candy, which has excellent potential to be marketed in the Burunan Murtajih Integrated Tourism Village. The main problem by the community so that ginger complex candy products attract consumers' attention is the use of proper packaging. This service activity aims to assist and guide PKK women in Murtajih Village to carry out attractive packaging as a marketing medium that can increase consumer attractiveness. The method of community service as a form of community empowerment is socialization and training to design the right packaging for ginger complex candy products. The results of the service activities, namely socialization activities, can increase the knowledge of PKK Murtajih Village women about packaging and packaging functions as indicated by the results of the pretest (45) and the posttest results increase to 90. By being provided with mentoring activities, PKK Murtajih Village women can interestingly do product packaging for ginger candy. The process of assisting in selecting the type of packaging suitable for ginger hard candies produces cylindrical bottle packaging. The packaging design is equipped with brand, composition, expiration date, PIRT number, product manufacturer name, and storage method. — Jahe dapat dimanfaatkan sebagai hard candy yang mempunyai potensi besar untuk dipasarkan di Desa Wisata Terpadu Burunan Murtajih. Permasalahan yang dihadapi masyarakat agar produk hard candy jahe menarik perhatian konsumen adalah penggunaan kemasan yang tepat. Tujuan kegiatan pengabdian ini yaitu memberikan pendampingan dan pembinaan kepada Ibu – Ibu PKK Desa Murtajih untuk melakukan pengemasan yang menarik sebagai media pemasaran yang mampu meningkatkan daya tarik konsumen. Metode pengabdian masyarakat sebagai bentuk pemberdayaan masyarakat adalah sosialisasi dan pelatihan mendesain pengemasan yang tepat untuk produk hard candy jahe. Hasil kegiatan pengabdian yaitu Kegiatan sosialisasi dapat meningkatan pengetahuan ibu-ibu PKK Desa Murtajih tentang kemasan dan fungsi kemasan yang ditunjukkan dengan hasil pretest (45) dan hasil posttest meningkat menjadi 90. Dengan diberikan kegiatan pendampingan, Ibu-ibu PKK Desa Murtajih dapat melakukan pengemasan produk permen jahe secara menarik. Pengemasan produk permen jahe disertai dengan desain kemasan yang telah dilengkapi informasi tentang merk, komposisi, tanggal kadaluarsa, nomer PIRT, nama produsen produk dan cara penyimpanan.